'Danian/Maastrichtian hiatus': A basin-wide event in the eastern Benin (Dahomey) Basin, Nigeria based on evidence from calcareous nannofossils. (July 2021) - Fadiya, S.L.; Coker, S.J.L.; Ekun, O.A.; Fadiya, M.O.; Ariyo, T.S.
Abstract: The calcareous nannofossil biostratigraphy of three wells (DB-1, DB-2 and DB-3) drilled along an approximate SWW–NEE trend in the eastern section of the Benin (Dahomey) Basin, Nigeria, has shown significant stratigraphic gaps in the sedimentary succession. In this study, we better constrained the presence and durations of four major hiatuses that occurred between the Late Cretaceous and late Miocene. Most conspicuous was an approximately 11.62 million-year hiatus spanning the Maastrichtian (Late Cretaceous, ~72.1 Ma) and Danian (Early Paleocene, ~60.48 Ma). The other unconformities identified occurred during the Eocene/Oligocene, Late Oligocene/early Miocene and middle/late Miocene. The presence of these unconformities across large areas of the basin is an indication of low sea levels and/or tilt in regional basin tectonics during the Late Cretaceous/Early Paleogene and has implication for stratigraphic trap styles for hydrocarbon exploration. Highlights: Nannofossil distribution in the late Cretaceous to late Miocene sequences of the Benin Basin, Nigeria. Delineation of the unconformities in the Benin Basin with emphasis on the absence of the Danian and Maastrichtian stages. Discussion on spread of unconformities in the Basin. Implication of the identified uncomformities for hydrocarbon play types.